Prediction of difficult mask ventilation in Thai adult patients undergoing elective surgery using ultrasound of distance from skin to hyoid bone, and from skin to thyroid isthmus: a prospective cohort observational study - Santi Anchalee; Kanatawan Wasoontrarak; Pannawit Benjhawaleemas; Sunisa Chatmongkolchart; Sumidtra Prathep (BMC Anesthesiology)
Abstract Background A previous study showed that airway ultrasound, specifically the distance from the skin to the hyoid bone (DSHB), may be correlated with a higher risk of difficult mask ventilation (DMV). However, the study was conducted in Italy and lacks data for the Asian and Thai populations. This study aimed to predict DMV using pre-operative ultrasonography to measure the DSHB and from the skin to the thyroid isthmus (DSTI) in Thai patients undergoing elective surgery under general anesthesia. Methods In total, 189 patients who underwent general anesthesia during elective surgery were enrolled in this prospective cohort observational study. Pre-operative physical examinations and airway evaluations were performed as usual. Airway ultrasound was performed to measure DSHB and DSTI before the anesthetic procedure. Anesthesiologists and nurse anesthetists performed bag-and-mask ventilation. DMV was assessed and recorded according to Han’s mask ventilation classification in which DMV-0 indicates no attempt at mask ventilation; DMV-I indicates successful ventilation by mask; DMV-II indicates ventilation by mask with oral airway/adjuvant ventilation; DMV-III indicates that ventilation required two providers; and DMV-IV indicates the patient’s inability to undergo mask ventilation. Results Thirty (17%) patients were classified as having DMV-0, and DMV-I, II, and III classifications were observed in 126(67%), 18(10%), and 12(6%) patients, respectively. None of the patients were classified as DMV-IV. The DSHB medians were 0.4(0.3–0.6), 0.7(0.5–1), 0.7(0.6–0.8), and 0.6(0.3–0.9) cm in DMV-0, I, II, and III, respectively (p < 0.001). The DSTI medians were 0.9(0.8–1.1), 0.8(0.7–1.1), 0.7(0.6–0.9), and 0.8(0.8–1.4) cm for DMV-0, I, II, and III, respectively (p = 0.041). Multivariate logistic regression indicated that the following factors were associated with difficult mask ventilation (DMV-III): male sex, modified Mallampati classification III, edentulousness, DSHB, and DSTI, with an area under the curve of 0.89. Conclusions This study showed that airway ultrasonography to determine DSHB and DSTI during patients’ routine physical examinations significantly improved the prediction of DMV. Patients classified as having DMV-III require prompt management for airway difficulties. However, the individual factors DSHB and DSTI alone are insufficient to predict DMV. Trial registration Registration number: TCTR2020093002.